The environment [1999 technology analysis and forecast]. - Betts, K.S.
This article presents an environment technology analysis and forecast for 1999. The subjects covered include end-of-life draft legislation, water treatment options, outsourcing liabilities, greenhouse gas reduction and design for environment concepts
Keywords: AD 1999.; Design for environment; Draft legislation; End-of-life.; Environment technology; Greenhouse gas reduction; Outsourcing liabilities; Technology analysis; Technology forecast; Water treatment